Illegitimate identity in the middle of an ideological crisis and tensions in the consumption network: a study on why plus-size fashion brands are illegitimate fashion elements - Zanette, Maria Carolina (2016)
This Dissertation explores why the plus size fashion field lacks legitimacy with plus size consumers. I have explored the subject in three papers. In the first paper, I study the process of legitimacy of a new emergent market, the Brazilian plus-size fashion market, and the challenges to institutionalization that it faces. I conducted seventeen interviews, performed netnography in four Brazilian plus-size fashion blogs and analyzed in a semiotic fashion an e-commerce shop that sells plus size fashion clothes. My results indicate that despite having legitimate actors promoting these plus size fashion brands, the plus size fashion field is still perceived as a shameful version of the fashion field. I argue here that the fact that one of the logics of the plus size fashion field being stigma, it affects derogatorily consumers’ identity projects in a way that prevents them from engaging in within the field cultural capital practices. In the second paper, I conducted a genealogical introspection in which I researched identity issues. As a (selfproclaimed) plus-sized woman I figured it would be relevant to look inside myself in order to explore how my identity entangles with the semiotic-material network that surrounds me in terms of both fashion, food and other elements. My data came both from concurrent and retrospective introspection techniques. In theoretical terms, I used the idea of assemblages and I focused my analysis both on the material aspects of my network of consumption and on the stability of this network. The consequences of my assemblage are linked to a total quality management of my identity, both online and offline, reflected on consumption practices that connect to the idea of a bulimic consumption logic on which food consumption and body management are interlinked. On my third paper, I examine the concept of identity from the perspective of plus size women´s consumption of fashion. Fourteen phenomenological interviews were conducted and analyzed from a hermeneutical perspective. Three thematic categories emerged from the data analysis: the construction of identity through fashion, elements of plus size identity and creative strategies to deal with the lack of products for plus size women in retail. Among the main results, the way the term plus size acts as stigma, influencing consumer´s identity projects, the role of retail in the stigmatization process and the shopping epic saga, which involves a ‘black market’ with the participation of sellers. Finally, I conclude discussing the role of identity in the instability of the plus size fashion field.